USE THE DRIS METHOD TO DETERMINE THE BEST NUTRIENTS BALANCE FOR CHICKPEA PLANTS THROUGH THE RELATIONSHIP BETWEEN NORMS AND CRITICAL POINT RATE - Y. A. A. Sabry; A. T. R. Dizayee (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to determine the best nutrient balance for chickpeas from the relationship between the Norms of nutrients with the critical point for each nutrient using the DRIS system. This experiment was carried out at the Grdarasha farm, college of Agriculture Engineering Science, University of Salahaddin during the spring growing season of 2020, to find out the effects of three levels of nitrogen (UREA) (0, 15, 30 Kg N ha-1), four levels of triple super phosphate (0, 20, 40, 60 Kg P ha-1), and three levels of KCl fertilizer (0, 15, 30 Kg K ha-1) and their combination on Chickpea yield and nutrient balance by using Split Split plot design with three replicates. The highest yield (1.55 Mg ha-1) was recorded from the lowest (2.02) AT or NBI (nutrient balance index), while the lowest yield (0.73 Mg ha-1) was obtained from the highest AT value (62.68).